Effect of Quercetin on Liver Oxidative Stress Parameters Induced by Butylparaben in Male Wistar Rats - Adegoke, Adebayo Olugbenga; Njoku, Rex; Bamigbowu, Olugbenga Emmanuel; Idung, Utibeabasi Idem (International Journal of Medical and Health Sciences Research, 2021)
Parabens are hormonally active chemicals widely used as preservatives in foods, cosmetics, toiletries and pharmaceuticals. Quercetin is a flavonoid with antioxidant property found in many fruits, plants and vegetables. The study investigated the effect of quercetin on the liver oxidative stress parameters induced by butylparaben in wistar rats. Thirty albino rats divided into six (6) groups of five rats were administered with 100mg/kg of butylparaben (BP), 100mg/kg of BP and 25mg/kg of quercetin (Q), 100mg/kg of BP and 50mg/kg of Q, 100mg/kg of BP and 100mg/kg of Q, 100mg/kg of BP and 200mg/kg of Q all dissolved in corn while the control were fed rat diet and water ad libitum with corn oil three (3) times weekly for sixty (60) days. The rats were sacrificed and liver harvested, homogenized and used for malondialdehyde (MDA), reduced glutathione (GSH), superoxide dismutase (SOD) and glutathione peroxidase (GPx) estimation using thiobarbituric acid method, Ellman’s method, epinephrine method and Rotruck et al method respectively while biuret and bromocresol green methods were used to estimate the blood Total protein and albumin levels respectively. The result showed significant difference(p<0.005) in concentrations of MDA (µmol MDA/mg protein) (2.62±0.44, 7.65±0.50 and 3.21±1.14), GSH (Units/mg protein) (12.65±1.52, 6.50±1.70, and 14.58±3.05), SOD (Units/mg protein) (90.67±8.30, 62.67±4.35 and 81.04±8.41),GPx (Units/mg protein) (1.16±2.81, 1.05±0.56 and 1.17±0.55), Total protein (g/L) (58.41±2.10, 55.08±3.60 and 58.41±2.10) and Albumin (g/L) (45.20±1.05, 40.69±4.82 and 42.14±1.51) for Control, (Bp) and (Bp+Q) respectively. The result has shown that quercetin caused a reversal of butylparaben-induced toxicity on liver oxidative stress parameters.